Narcissism and leadership - Zivkovic Rancic, Zana J. (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2025)
Every person, and especially a leader in an organization, should have a healthy dose of narcissism in their personality to persist. Leadership is becoming more recognized as a key issue for companies facing change in a complex and evolving environment. This leads to the need to understand the extensive literature on leadership. However, it is notable that the literature is primarily focused on effective leadership, ignoring the dark side of it. However, research in the field of change has shown that such toxic forms of leadership negatively affect the capacity of organizations to adapt to change. If traits associated with narcissism are also associated with ineffective leadership, the real question is why are narcissistic personalities often found in leadership positions? One possibility is that narcissists have skills and traits that are necessary for emerging leaders, but are not necessarily useful for effective leadership. In other words, narcissism might predict leader emergence, but not necessarily their effectiveness. This paper is an attempt to systematize previous theoretical and practical findings in the field of narcissism and leadership, as well as their mutual connection.